Lock & key : the secrets of locking things up, in, and out - Tchudi, Stephen, 1942- (Charles Scribner's Sons ; Maxwell Macmillan Canada ; Maxwell Macmillan International, 1993)
Describes the development and uses of different kinds of locks, relates stories about important locks in history, and discusses the meanings that the words "lock" and "key" have taken on in our language.